Hydrogen & hydrogen energy creating the universe: Spin-Top Theory. (28th February 2020) - Veziroğlu, T. Nejat
Abstract: Using the Spin-Top Theory of the universe, and the available information about the universe, the characteristics of the universe-seed (or U-Seed), creation of the universe and its life cycle have been estimated. With the explosion of the U-Seed, made of hydrogen, hydrogen and its thermonuclear reaction products start spreading, and forming an ever growing ellipsoid on the way out, while circling the universe center (U-Center). Then, as a result of the gravitational pull, heavenly bodies start moving towards and eventually reaching the universe center (U-Center) to reform the U-Seed. During this expansion and contraction periods, the universe boundaries and the pertinent times have been calculated. It is shown that a universe cycle is about 148 billion years, and it repeats itself forever. Graphical abstract: Image 1 Highlights: Spin-Top theory of the universe is developed using the available information about the universe. It explains the observed features of the universe better than the Big Bang theory. Universe consists of infinite number of cycles, with a cycle period of 148 billion years. Universe is the only perfect perpetual motion machine.